SP0013 Widespread cutaneous thickening – could this be early diffuse cutaneous systemic sclerosis?. (15th June 2017) - Suarez, A
Abstract : A case of diffuse sclerosing skin disease shall be presented. The features that initially led the treating team to consider a diagnosis of systemic sclerosis shall be discussed, alongside subsequent features that emerged that cast doubt over this diagnosis and led the team to undertake additional investigative studies. The presentation shall provide a chronological description of the clinical features, laboratory studies, microvascular imaging and histological studies that helped the team to reach a definitive diagnosis and plan management accordingly. Disclosure of Interest: None declared